Bokhögstubbar i Klåveröds strövområde : utbredning, egenskaper och betydelse för rödlistade vedlevande skalbaggar - Holmström, Emma (SLU/Southern Swedish Forest Research Centre, 2006)
Lack of dead wood is the main cause of decaying or loss of populations for many forest species. To increase the amount of dead wood is a prerequisite to maintain biodiversity in forests of northern Europe. In summer 2006 the recreation area Klåveröd, at Söderåsen in Skåne, Sweden, has been inventoried for high stumps (snags) of beech, (Fagus sylvatica). The result of the inventory has been compared with data of the real estate and forest management directories from the owner, region Skåne. The results have also been matched with the results from an inventory of saproxylic beetles in 2005, performed with windowtraps on selected snags both in the area and the adjacent national park Söderåsen. 594 snags were found on 747 ha. 80% of the number of snags were found on forestground, others on wetland or steep slopes. 30 % were situated in areas for nature conservation; NS and NO, even though these areas only represented 9% of the area. The number of snags were the same for the northern and southern part of Klåveröd but less redlisted saproxylic beetles were found in the northern part and there were less old decaying snags which could indicate a shorter period of snag existence. The southern part of Klåveröd borders to Söderåsen national park which could be the main factor of the gradient in redlisted species abundance. Furthermore the snags in northern Klåveröd are separated from the southern parts by a barrier of conifer stands of one kilometre width. The lack of continuity in dead wood and the limited dispersal ability from known habitats is the primary difference between the two parts of Klåveröd and also the gradient between Klåveröd and the national park.